Perfectionist Liberalism and Political Liberalism. (Part II) - Nussbaum, Martha C. (2017)
In the first part of the article, the author discusses two types of liberalism from the thoughts of prominent philosophers. On the one hand, she analyzes the ideas of Isaiah Berlin and Joseph Raz as examples of perfectionist liberalism and, on the other hand, those of John Rawls and Charles Larmore as examples of political liberalism. He then discusses the notion of comprehensive doctrines in John Rawls’s oeuvre, for from Nussbaum´s perspective, the construction of this notion brings Rawls close to a variant of perfectionist liberalism that he himself would try to avoid. That is why Nussbaum’s proposal is to restore a notion of comprehensive doctrines simply understood as those kinds of doctrines to which reasonable citizens adhere.